Audio frequency analyzer - Lee, Liang De (2015)
The most primitive way of looking at waveforms is in its time domain – looking at how the signal changes in amplitude as time passes. This is normally observed through an oscilloscope, and it is quite natural for us to look at waveforms through an oscilloscope display. However, signals can be displayed in other ways such as in the frequency domain. Jean Baptiste Fourier, a French mathematician and physicist, started to observe how signals are seen in the frequency domain, where signals are viewed as a function of their frequency rather than time. He discovered that any waveform seen in the time domain, there is an equivalent representation in the frequency domain. Meaning that, any signal is made up of many different frequencies, i.e. square waveform are made up of multiple sine waveforms. By observing signals in the frequency domain with a spectrum analyzer enables us to analyze the harmonic and spurious content of a signal. Also the width of signals when modulated has been applied is important for developing Radio Frequency (RF) signal sources, and especially any form of transmitter including those in cellular, Wi-Fi, and other radio or wireless application. In this project, I will be focusing on creating a device capable of sampling audio frequencies in the human audible range.